Isolated, reduced diffusing capacity for carbon monoxide in the population – relations to symptoms, smoking and comorbidities - Viktor Hamrefors; Johan Westerbergh; Annelie Behndig; Anders Blomberg; John Brandberg; Anna Carlén; Arne Egesten; Emil Ekbom; Össur Ingi Emilsson; Maria J. Eriksson; Andreas Frølich; Ludger Grote; et al. (BMC Pulmonary Medicine, 2026)
Abstract Background Diffusing capacity for carbon monoxide (D LCO ) is a measure of gas exchange in the lungs. Reduced D LCO with normal spirometry is a common finding that is incompletely understood. Aim To assess determinants of isolated, reduced D LCO in an unselected population. Methods The Swedish CArdioPulmonary bioImage Study (SCAPIS) is a multicentre population-based study of adults aged 50–64 years. The 5th percentile of D LCO in healthy never smokers was used as the lower limit of normal (LLN). Using multivariable analysis, we studied factors associated with D LCO < LLN in 24 261 subjects with normal spirometry, defined as FEV1, FVC and FEV1/FVC > LLN. Emphysema and interstitial lung abnormalities (ILA) were assessed through computed tomography, physical activity through accelerometry and other factors through questionnaires. Results Isolated D LCO < LLN ( n = 1 472) was independently associated with emphysema (odds ratio and 95% confidence interval: 2.6 (2.2, 3.2)), lung disease other than asthma or COPD (1.8 (1.2, 2.8)), exertional chest pain (1.6 (1.3, 2.1)), smoking (per-10-pack-years) (1.6 (1.4, 1.9)), ILA (1.4 (1.2, 1.7)), breathing problems (1.4 (1.1, 1.8)), male sex (1.3 (1.1, 1.6)) and coughing (1.2 (1.1, 1.5)). D LCO < LLN was less likely if subjects were older, had asthma or had higher BMI, haemoglobin, FVC or physical activity. Conclusion Isolated, reduced D LCO in a large middle-aged population cohort is associated with numerous previously known factors, including emphysema, ILA, smoking and self-reported lung disease. However, several symptoms, including exertional chest pain, breathing problems and coughing, are also independently associated with isolated reduced D LCO .